Prevention of trastuzumab-related cardiotoxicity in HER-2 positive breast cancer patients. (4th February 2022) - Ferri, L; Bergamini, C; Springhetti, P; Niro, L; Cerrito, LF; Schiavone, A; Dal Porto, M; Setti, E; Benfari, G; Rossi, A; Fiorio, E; Ribichini, FL
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Trastuzumab (TZ) is a key therapy for HER-2 positive breast cancer that may have different side effects on the cardiovascular system. One of the most concerning complications is cancer therapy-related cardiac dysfunction (CTRCD). In literature there are conflicting data about the efficacy of heart failure drugs like ACE-inhibitors, ARBs and beta-blockers to prevent such an event.  Purpose: Aim of this study is to describe our experience on cardioprotective drugs in preventing TZ-related CTRCD. Methods: 105 consecutive women affected by HER-2 positive breast cancer treated with TZ referring to our echo-lab were enrolled in our single center prospective study. 3 patients were excluded due to an early TZ suspension not related to cardiovascular complications. Thus 102 patients (97, 1%) were eligible for analyses. 86 of these (84, 3%) were also treated with Anthracyclines. All patients underwent consecutive transthoracic echocardiography (TTE) before starting TZ and then every 3 months up to 12 months. 2D-Speckle tracking analysis was performed at baseline and at each examination using Tomtec software. A complete clinical evaluation was also performed at each follow up. LV systolic dysfunction was defined as an absolute reduction of LVEF >10% from baseline to LVEF < 53% or a relative reduction of GLS >15% from baseline and a reduction of LVEF >10% from baseline.  Results: Overall, before starting TZ, 12 patients were taking ACE-inhibitors or ARBs (11, 8%) and 5 patients beta-blockers (4, 9%). CTRCD occurred in 11 patients (10, 8%), among these 9 (81, 8%) weren't taking any heart failure drugs and 5 (45, 5%) didn't present any cardiovascular risk factor. We observed no significant association among cardiovascular risk factors.  Use of potential cardioprotective drugs before TZ administration seems to reduce the risk of development of myocardial dysfunction (relative risk 1, 67; 95% confidence interval [CI], 0, 41 to 6, 82; P > 0.05). No clear association was found between any cardiovascular risk factors and CTRCD (relative risk 0, 81; 95% confidence interval [CI], 0, 26 to 2, 47; P > 0.05). Conclusions: In HER-2 positive breast cancer patients treated with TZ an early treatment with ACE-inhibitors or ARBs and/or beta-blockers is associated to the prevention of CTRCD. CTRCD seems not to be related to the presence of cardiovascular risk factors.